2018
DOI: 10.1038/s41467-018-05793-2
|View full text |Cite|
|
Sign up to set email alerts
|

The VAR2CSA malaria protein efficiently retrieves circulating tumor cells in an EpCAM-independent manner

Abstract: Isolation of metastatic circulating tumor cells (CTCs) from cancer patients is of high value for disease monitoring and molecular characterization. Despite the development of many new CTC isolation platforms in the last decade, their isolation and detection has remained a challenge due to the lack of specific and sensitive markers. In this feasibility study, we present a method for CTC isolation based on the specific binding of the malaria rVAR2 protein to oncofetal chondroitin sulfate (ofCS). We show that rVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 59 publications
2
113
0
Order By: Relevance
“…In the second step, putative CTCs are further stained and identified using anti-cytokeratin antibodies while contaminant white blood cells (WBCs) are identified by means of CD45 staining. Currently, CellSearch is the only CTC isolation device that is approved by the US Food and Drug Administration (FDA) [5], although "sister" antigen-based CTC isolation technologies are continuously emerging [6,7]. CellSearch has been validated in large patient cohorts, and its main use concerns CTC enumeration to identify high-risk patients with decreased progression-free survival and decreased overall survival in breast, prostate, and colorectal cancers [5,8].…”
Section: Ctc Isolation Technologiesmentioning
confidence: 99%
“…In the second step, putative CTCs are further stained and identified using anti-cytokeratin antibodies while contaminant white blood cells (WBCs) are identified by means of CD45 staining. Currently, CellSearch is the only CTC isolation device that is approved by the US Food and Drug Administration (FDA) [5], although "sister" antigen-based CTC isolation technologies are continuously emerging [6,7]. CellSearch has been validated in large patient cohorts, and its main use concerns CTC enumeration to identify high-risk patients with decreased progression-free survival and decreased overall survival in breast, prostate, and colorectal cancers [5,8].…”
Section: Ctc Isolation Technologiesmentioning
confidence: 99%
“…Overall, so far there is no hard evidence for the prognostic advantage of the EpCAM-independent approaches in BC. Interestingly, there might be another way to bypass the problems with EpCAM-dependent isolation: finding some other, more universally expressed marker, like, for example the malaria protein VAR2CSA [108].…”
Section: Current Technical Limitations In Ctc Clinical Researchmentioning
confidence: 99%
“…Targeting oncofetal chondroitin sulfate (ofCS) by the malarial recombinant VAR2CSA (rVAR2) protein might hold potential as a near-universal CTC-targeting agent as it binds to cancer cells independently of tumor origin. Furthermore, we have previously shown that rVAR2 binding to cancer cells is unaffected by cell plasticity such as epithelial-to-mesenchymal transition (EMT) [26]. This is an important trait since EMT is indicative of increased metastatic capacity of CTCs [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our initial CTC studies have shown promise for an rVAR2-based capture method, yet several technical aspects of the method remain unexplored. Previous clinical CTC data was based on the DBL1-ID2a (121 kDa) rVAR2 construct, but for this optimization study we also included the smaller ID1-ID2a (70 kDa) construct (Figure 1a) [26]. Both recombinant forms of rVAR2 are well defined in terms of ofCS specificity and affinity [19].…”
Section: Recombinant Var2csa Can Be Efficiently Coupled To Sera-mag Bmentioning
confidence: 99%